Capital Structure Changes Prior and Post Initial Public Offering: Empirical Evidence from the Indonesia Stock Exchange - Dhita, Sasha; Azam Achsani, Noer; Sembel, Roy; Purwanto, Sugeng (International Journal of Engineering and Technology, 2018)
The changes in capital structure following Initial Public Offering (IPO) is expected to improve the financial performance of the company, but post IPO capital structure is not enough to provide certainty that the company will have a better financial performance. The evaluation of the financial performance of the company following IPO has become one of the focuses of attention both from managers and investors. This study aims to analyze the capital structure changes for non-financial companies listed on the Indonesia Stock Exchange prior and post IPO using t-test analysis, and descriptive statistics analysis of Net DER prior and post IPO both for overall market and individual industry. The data sample includes 74 non-financial companies conducting IPO in the period of 2003 until 2012. The capital structure measurement adopted in this study is net debt-to-equity ratio (Net DER) and this study evidenced that for overall market, there is a significant decrease of average Net DER following IPO. On the other hand, this study evidenced that for overall market, the median Net DER stayed at around 0.3 following the IPO, which showed that following IPO the companies utilized their additional debt capacity to go back to their pre-IPO level.Â Â